2013
DOI: 10.1016/j.dcn.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Biological impact of preschool music classes on processing speech in noise

Abstract: Musicians have increased resilience to the effects of noise on speech perception and its neural underpinnings. We do not know, however, how early in life these enhancements arise. We compared auditory brainstem responses to speech in noise in 32 preschool children, half of whom were engaged in music training. Thirteen children returned for testing one year later, permitting the first longitudinal assessment of subcortical auditory function with music training. Results indicate emerging neural enhancements in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 86 publications
(107 reference statements)
3
58
1
4
Order By: Relevance
“…Based on previous reports, we also predicted that musical training would not affect all components of the response equally (reviewed in Kraus and Chandrasekaran, 2010; Kraus et al, 2012; Strait and Kraus, 2013). Consistent with our predictions, we observed differences between musicians and the general population for response latency, high-frequency phase-locking, and response consistency—three aspects of the cABR previously shown to be enhanced in musicians (Musacchia et al, 2007; Parbery-Clark et al, 2009a, 2012a,b; Strait et al, 2012b, 2013a,b). Across these different subcomponents of the response, the effect of musicianship appears most evident for younger and older age groups, with minimal differences for the adolescents and young adults (<40 years old).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on previous reports, we also predicted that musical training would not affect all components of the response equally (reviewed in Kraus and Chandrasekaran, 2010; Kraus et al, 2012; Strait and Kraus, 2013). Consistent with our predictions, we observed differences between musicians and the general population for response latency, high-frequency phase-locking, and response consistency—three aspects of the cABR previously shown to be enhanced in musicians (Musacchia et al, 2007; Parbery-Clark et al, 2009a, 2012a,b; Strait et al, 2012b, 2013a,b). Across these different subcomponents of the response, the effect of musicianship appears most evident for younger and older age groups, with minimal differences for the adolescents and young adults (<40 years old).…”
Section: Discussionsupporting
confidence: 90%
“…We have used this stimulus for nearly a decade as part of the standard protocol administered to all study participants and over time we have amassed a large dataset from a wide range of participants, enabling us now to provide the first comprehensive examination of how musicianship affects auditory brainstem function throughout life. It is important to note that although we have repeatedly demonstrated musician enhancements for longer speech stimuli (Wong et al, 2007; Parbery-Clark et al, 2009b, 2012b,c; Strait et al, 2012b, 2013a,b), we have not previously seen differences between “musicians” and “non-musicians” for this exact stimulus and collection protocol (unpublished data). However, previous analyses used small groups of participants within narrow age ranges.…”
Section: Introductionmentioning
confidence: 51%
“…Further, musicians demonstrate enhanced auditory cognitive function such as working memory [32][33][34] and attention [6,35,36], as well as enhanced neural representation of speech when presented in acoustically-compromised conditions [6,8,9,[37][38][39][40]. These findings are consistent with the theoretical framework proposed by Patel suggesting that music training promotes adaptive plasticity in speech-processing networks [41].…”
Section: Introductionsupporting
confidence: 86%
“…There is strong evidence from previous cross-sectional studies comparing adult musicians and nonmusicians that long-term music training promotes brain plasticity (Münte, Altenmüller, & Jäncke, 2002) in modifying the functional (Schneider et al, 2002;Pantev et al, 1998) and structural (Elmer, Hänggi, Meyer, & Jäncke, 2013;Gaser & Schlaug, 2003;Schneider et al, 2002) architecture of the auditory pathway. Results of longitudinal studies, mostly in children, showed that music training can be the cause of the observed effects (François, Chobert, Besson, & Schön, 2013;Strait, Parbery-Clark, O'Connell, & Kraus, 2013;Chobert, François, Velay, & Besson, 2012;Moreno et al, 2011;Hyde et al, 2009;Moreno et al, 2009). Most importantly for the present purposes, there is also evidence that music training improves different aspects of speech processing (for review, see Asaridou & McQueen, 2013;Kraus & Chandrasekaran, 2010).…”
Section: Introductionmentioning
confidence: 99%